A Comparative Study on Serum Levels of "Thymic Stromal Lymphopoietin" Between Patients with Psoriasis Vulgaris and Healthy Individuals: A Case-Control Study - Siri Sri Kollabathula; Konakanchi Venkatachalam; Kethireddi Susmitha Divya; Patnala Guruprasad; Pallapati Anila Sunandini Nayar (Wolters Kluwer Medknow Publications, 2024)
Background: Thymic stromal lymphopoietin (TSLP) is a cytokine initially implicated to be associated with allergic disorders inducing Th2 response. Emerging studies have shown that TSLP is also involved in autoimmune diseases. In psoriasis, TSLP acts in synergy with T cell-derived CD40L to promote the release of IL-23 from dendritic cells. IL-23 is responsible for the inappropriate immune reaction and keratinocyte proliferation in psoriasis. Targeting TSLP could be a novel therapeutic approach in the treatment of psoriasis. Objective: To compare the serum levels of TSLP between patients with psoriasis and healthy individuals. Materials and Methods: A prospective hospital-based case-control study was carried out on 38 patients with psoriasis. The severity of psoriasis was graded into mild, moderate, and severe according to PASI. A total of 30 healthy individuals with matched age and sex were taken as controls. 5 ml of venous blood was collected, centrifuged, and the collected serum was stored at -80°C until quantitative assessment by sandwich enzyme-linked immunosorbent assay (ELISA) technique. Results: TSLP has been found to be significantly elevated in the sera of cases (0.1380178 pg/ml) than in controls (0.1125974 pg/ml). There was also a significant proportionate increase in the mean TSLP with the mean PASI score. Limitations: The sample size was small and we could not follow-up the cases to study the changes in TSLP levels with remission of the lesions. Conclusion: We found that serum TSLP was elevated in psoriasis patients and correlated with disease severity, indicating a possible pathogenetic role.